2019
DOI: 10.3389/fmicb.2019.01575
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Survey of Fungi in the Human Gut: ITS Profiling, Phenotyping, and Colonization

Abstract: The fungal component of the intestinal microbiota of eight healthy subjects was studied over 12 months using metagenome survey and culture-based approaches. Aspergillus , Candida , Debaryomyces , Malassezia , Penicillium , Pichia , and Saccharomyces were the most recurrent and/or dominant fungal genera, according to metagenomic analysis. The biodiversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
103
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(110 citation statements)
references
References 41 publications
(76 reference statements)
5
103
2
Order By: Relevance
“…Such association between feed and fungal gut might also apply for the plant pathogens Ustilago hordei and Mycosphaerella tassiana, found in about 3% of the animals. Former results are in agreement with previous reports on humans and nonhuman primates (Hallen-Adams et al 2015;Mann et al 2019;Nash et al 2017;Raimondi et al 2019), and suggest that, differently to pig gut prokaryotes (Xiao et al 2016), the pig gut mycobiome may lack a stable core. Consequently, it is expected that a large proportion of the fungi detected in pig fecal samples may be transients from dietary or environmental origin.…”
Section: Discussionsupporting
confidence: 92%
“…Such association between feed and fungal gut might also apply for the plant pathogens Ustilago hordei and Mycosphaerella tassiana, found in about 3% of the animals. Former results are in agreement with previous reports on humans and nonhuman primates (Hallen-Adams et al 2015;Mann et al 2019;Nash et al 2017;Raimondi et al 2019), and suggest that, differently to pig gut prokaryotes (Xiao et al 2016), the pig gut mycobiome may lack a stable core. Consequently, it is expected that a large proportion of the fungi detected in pig fecal samples may be transients from dietary or environmental origin.…”
Section: Discussionsupporting
confidence: 92%
“…The second reason for the observed differences has been attributed to differences in cohort characteristics, such as diet and/or geographical location. Strati (2016) and Raimondi's (2019) investigating cohorts in Italy, detected same dominant fungal genera [58,61], and the investigation of cohorts in two different states in the USA observed different results [6,45]. We used ITS1 and ITS4 in this study and found that the genera Pichia, Candida and Cladosporium dominated the urban cohort, whereas genera Pichia, Candida and Aspergillus dominated the rural cohort.…”
Section: Discussionmentioning
confidence: 64%
“…A review of the literature suggest that C. albicans carriage in healthy individuals ranges from 30-60% [68] and that living mammals are considered a niche for these species as they are not found in signi cant concentrations in soil, food or air [69,70]. reported that C. albicans was frequently detected and dominated the cultivable mycobiota of different faecal samples [61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Candida albicans is a commensal fungus that colonizes the GI tract of ~60% of the human population (Raimondi et al, 2019). Although a major colonizer of humans, its role as a commensal microbe is largely uncharacterized.…”
Section: Introductionmentioning
confidence: 99%